Co-Constructing Culturally Sustaining Practices for Fostering Young Children's Literacy in Fiji. Issue 1 (2nd January 2020) - Harris, Pauline; Brock, Cynthia H.; McInnes, Elspeth; Diamond, Alexandra; Neill, Bec; Carter, Jenni; Giannakis, Eleni
ABSTRACT: This article reports a three-year, cross-cultural study on co-constructing culturally sustaining pedagogic (CSP) practices with children and their families and communities, to foster children's literacy in their home languages and English in Fiji's settings. As we argue in this article, dialogue is a vital part of CSP – specifically, authentic dialogic encounters defined as educative encounters with people in and about their worlds, occurring in relational contexts infused with an ethics of care and commitment. The study was framed as critical participatory action research. We present key findings focusing on: ensuring contextual relevance and responsiveness of pedagogic practices, co-constructing CSP practices with children and their families and communities, and documenting children's learning and engagement through culturally inclusive means. We close with discussion about how authentic dialogic encounters served to move toward four tenets of CSP: (1) outcomes must be pluralist, (2) avoid essentializing culture and race, (3) focus on traditional languages and cultures in dynamic ways, and (4) take an inward gaze.